EFFECTS ON HAEMATOLOGICAL PARAMETERS OF CUCURBITA PEPO SEEDS IN RABBITS. - Yasmin Shaikh1 , Ahsan Aslam2 , Kahaf Khan3 , Rukhsana Malik4 , Kashif Rasheed Shaikh5 , Habibullah Shaikh6 , Ghulam Mustafa Dahri7 , Ali Gul Tunio8 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Medicinal plants chemical constituents affect body systems.1,2 Cucrabitaceae belongs to the plant family, generally believed as consisting of melons, cucurbits and pumpkin. OBJECTIVE: Assessment of effects of cucurbita pepo (pumpkin) seeds on haematological parameters in rabbits. DESIGN: Experimental study. PLACE: The study was conducted at the Pharmacology Department PUMHSW Shaheed Benazirabad. DURATION 01st Jan 2020 to 31st March 2020. MATERIAL METHODS: By observing standard criteria for inclusion and exclusion of rabbits in study. Thirty rabbits were chosen in the study. Calculated quantity of powder of pumpkin seeds as 250 and 500 mgs was given subsequently daily for sixty days to study groups. Zero time had reading marked as day 1st. Thereafter further readings taken after every 15th day for the two months. The samples were assessed at D and R Lab PUMHS Shaheed Benazirabad. Blood CP analyzed through Automatic Hemoglobin Analyser. Data evaluated statistically in groups as means by the correlated pairs T-test and SPSS 22.0 version. P-value upto 0.05 considered significant. RESULT: Whilst compared the study groups (B and C) with the control (A) group the mean Hb, RBC, HCT, MCV, MCH and MCHC values on day 0 were found non significant statistically. An increasing increase was observed from day 15 to day 60 in all blood parameters. As compared with the control group, all interpretations were highly statistically significant. CONCLUSIONS: Pumpkin seed can be substituted by common methods as good herb food source for the boosting hemoglobin marker. It does not carry side effects of weight increase or non cooperation of patients wih medical treatment due to higher cost or having adverse effect.